Navigating Globalization: An In-depth Analysis of China's Media Regulation in the Face of Economic and Technological Transformation - Narang, Bernika Yustisiana (International Journal of Social Service and Research, 2024)
The research investigates the intricate interplay between globalization, the dynamics of the media industry, and regulatory frameworks, with a specific focus on China. Employing the literature review method, this study aims to provide a nuanced understanding of how globalization influences media law, regulation, and governance. It explores the repercussions of economic global integration and technological advancements, with China as a case study. Special attention is given to the multifaceted impact of globalization on the complex fabric of media regulation in China. Economic globalization and technological progress are identified as pivotal factors shaping regulatory frameworks. The research not only examines challenges but also explores potential opportunities for synergy between global forces and national regulatory structures. The findings, including globalization's significant impact on the media industry, especially in the Chinese context, especially in the Chinese context, contribute to the existing knowledge by shedding light on how nations navigate the delicate balance between global interconnectedness and the preservation of distinctive media regulatory landscapes. This study holds significance for scholars, researchers, and policymakers grappling with the evolving global media landscape.